PENGARUH TINGKAT BAGI HASIL, NON PERFORMING FINANCING, DANA PIHAK KETIGA, DAN FINANCING TO DEPOSIT RATIO TERHADAP PEMBIAYAAN BAGI HASIL PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2011-2015 - Surya Rizky Oktovan, 13.05.52.0153; Aini, Nur (Students Journal of Accounting and Banking, 2017)
Aimed of this research are to analyze the influence level of profit sharing, non-performing financing, third party funding and financing to deposit ratio to finance towards financing profit sharing on Islamic Banks in Indonesia 2011-2015. This research was conducted in Islamic Banks registered in Financial Services Authority. The populations in the study is the islamic Bank in Indonesia 2011-2015 which reported financial statement at OJK. The Sampling method used purposive sampling period study from 2011 to 2015 with 171 samples. The method used is the panel data regression The result showed that 1) the level of profit sharing that has positive effect was not significant 2) The positive effect of Non performing financing is significant 3) Third party funds has significant positive effect 4) Financing to deposit ratio that has positive effect is not significant to financing profit sharing of Islamic Banks in Indonesia in 2011-2015.Keywords: Level of Profit Sharing, Non Performing Financing, Third Party Funds and Financing to Deposit Ratio